Chemomechanical Instabilities in Responsive Materials - Borckmans, P.; Kepper, P.; Khokhlov, A. R.; Mťens, S. (NATO Science for Peace and Security Series A: Chemistry and Biology, 2009)
This volume contains a selection of the papers presented by renowned specialists of each field. It is the first book in which the communities of nonlinear chemists and gel specialist communicate and show how interactions between the two fields can actually produce working devices based on the transduction of chemical to mechanical energy and vice-versa. Beside subtle ways of using the slaving of responsive materials devices to oscillatory reactions, emphasis is brought on emerging properties that are possessed by neither of the separated constituents. Several contributions on these aspects are included, in relation to their potential relevance to biological, medical and technological applications. The whole constitutes a specific multidisciplinary "new" field. Both advanced and basic aspects of the two fields can be found the this collection of lectures. The book will not only benefit to doctoral students or young post-docs to learn the ropes of both subjects, but also to active researchers from one field, to "catch up" on the other without getting lost in the huge literature that exists in each of the particular fields.